Pengolahan Fasa untuk Mendapatkan Model Tinggi Permukaan Dijital (DEM) pada Radar Apertur Sintetik Interferometri (INSAR) Data Satelit - Ishak Hanafiah Ismullah (Journal of Mathematical and Fundamental Sciences, 2004)
Comparing to optical sensors, radar technology has only just begun. Mapping by optical sensors, especially with Photogrammetric methode shows a very good result, but the main constraint is cloud cover conditions, and this was the weakness point of the Photogrammetric techniques. Indonesia is a tropical country which has dominant cloud coverage, and some of the area has cloud cover almost all year long. Radar imaging has some advantages e.q. sun independence, cloud penetration etc. Active systems in ERS1, ERS2, RADARSAT, JERS, and ENVISAT make possible to do interferometric processing. This paper try to explain how to process phase information from radar satellite data especially from ERS1 and ERS2. The result has been compared with the Digital Photogrammetric technigue, for Papandayan and Cikurai vulcano, West Java.